Proliferation and apoptosis in subcutaneous adipose tissue of lactating cows with different genetic merit for milk yield. Issue 1 (February 2017) - Colitti, Monica; Pošćić, Nataliya; Stefanon, Bruno
Highlights: Cows with high genetic merit (EBVp) had a significantly higher fat, protein and milk yield in comparison to cows with low genetic merit (EBVm). Adipocyte sizes were significantly larger in EBVm cows. Apoptosis was significantly higher in adipocytes of EBVm cows. DLK-1 protein expression was clearly evident in adipocytes of EBVp cows. Milk yield genetic merit of cows is related to subcutaneous adipose tissue cellularity and fat metabolism. Abstract: The aim of this study was to investigate the adipocyte size and fate in subcutaneous fat (scAT) of cows diverging for genetic merit at mid lactation stage, when anabolic activity increases and animals are in a state of positive energy balance. Twenty mid lactation cows (180 ± 20 days in milk) grouped according to the Estimated Breeding Values (EBV) for milk yield in plus (EBVp) and minus (EBVm) variants were selected. Average of adipocytes area, proliferation and apoptotic labelling index as well as DLK-1 expression, a marker of pre-adipocytes, were immunohistochemically evaluated in scAT biopsies. In EBVp cows, the BCS was lower ( P < 0.01) whereas milk yield, protein, fat yield ( P < 0.001) and plasma free fatty acid concentration ( P < 0.05) were higher. The scAT of EBVp cows showed a significantly ( P < 0.001) higher frequency between 500 and 3000 μm 2 classes in comparison to EBVm cows, that showed a significantly ( P < 0.01) higher apoptotic labeling index. The immunohistochemical reaction showed DLK-1 positivity in scAT of EBVp cows. Taking together, the data indicate a link between milk yield genetic merit of cows, scAT morphology and function, suggesting greater dynamics and metabolic flexibility in EBVp cows.